Compreensões e escolhas de um grupo de gerentes de um hospital de alta complexidade sobre estratégias de melhoria da gestão - Barros, Dione Bezerra de (2010)
The high complexity level of hospital management requires a great deal of creativity on the part of hospital managers and administrators so as to identify strategies leading to the expected outcomes which also face up to the countless challenges renewedly arising in the institutions’ daily routine. Hospital management strategies are directly influenced by the context where the organization belongs. Services management cannot ignore sociopolitical factors which determine their activities directions, but they find themselves being questioned about their techno-managerial readiness for finding ways to solve the difficulties which may arise. This study aims at analyzing what services managers say regarding strategies for enhancing management in a high complexity hospital in Ceará. It is an evaluative research, which used quality approach, and was carried out among six services managers of Hospital Dr. Carlos Alberto Studart Gomes, Fortaleza, Ceará, from May 3rd to June 30th, 2010. Recorded individual interviews were held, with narrative transcriptions and later content analyses. The selected participants were managers with at least a 2-year experience in the position. The following units of meaning have been set: hospital management strategies; motivation for hospital management strategies choices; hindering aspects in hospital management; and facilitating aspects in hospital management. The managers reported that choices regarding the strategies for the enhancement of the hospital management vary due to their educational background and what they have experienced both personally and professionally. They highlighted as being relevant the strategies related to people management, the use of indicators, leadership practice, and the interaction of processes, all of them guidelines for the Public Management Excellence Model (in Portuguese, Modelo de Excelência em Gestão Pública – MEGP). We could infer that the manager needs to be skilled to work the intersubjectivity within the groups, otherwise he/she will not be successful in the strategies he/she adopted, which may cause him/her difficulties while resolving situations, including faulty communicational processes that keep people away from the organizational targets. We regard as indispensable greater investment in the managers’ theoretical and practice formation for facing the huge challenge of hospital management.